1991
DOI: 10.1093/rheumatology/30.1.45
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Use of a Patient Knowledge Questionnaire in Rheumatoid Arthritis

Abstract: A multi-choice Patient Knowledge Questionnaire (PKQ) was developed for use with patients with rheumatoid arthritis (RA). Test/re-test was used to test its stability (r = 0.81), and Kuder Richardson formula 20 (r = 0.72) for internal consistency. Seventy randomly selected RA patients then completed the PKQ in a rheumatology out-patient clinic of a large teaching hospital. There was a wide variation in total scores ranging from 3 to 28 out of 30. Total scores correlated with years of general education (P less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
80
3
17

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 0 publications
15
80
3
17
Order By: Relevance
“…People also want to make the decisions about everyday problems, emphasizing the need for effective education in self management approaches. Another key finding of our study was that patient knowledge of RA is limited, as found in previous studies (21,22). We found that older age, male sex, and lower level of formal education were associated with low RA knowledge scores.…”
supporting
confidence: 77%
“…People also want to make the decisions about everyday problems, emphasizing the need for effective education in self management approaches. Another key finding of our study was that patient knowledge of RA is limited, as found in previous studies (21,22). We found that older age, male sex, and lower level of formal education were associated with low RA knowledge scores.…”
supporting
confidence: 77%
“…No correlation was found between duration of the disease and knowledge of the disease, unlike what was seen in the British study, and in other studies on individuals with rheumatoid arthritis 20,21 and psoriatic arthritis. 22 The questionnaire showed satisfactory levels of inter and intraobserver reliability, with r = 0.813 and r = 0.790 for the two analyses, with high correlations.…”
Section: -13contrasting
confidence: 78%
“…Additionally, 73.6% of the patients were men. With regard to ethnicity, 59.5% were white, 5.2% black, 20.7% mixed race and 14.6% other ethnicities, such as brown and Asian. Axial disease was observed in 36.7% and axial involvement associated with peripheral and enthesis joints in 7.9%.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge was measured using the Patient Knowledge Questionnaire (PKQ) (Hill et al, 1991) which assesses patient knowledge in 4 areas; disease process, drug therapy, exercise and joint protection techniques. PKQ scores range from 0 30 with higher scores reflecting greater knowledge.…”
Section: Outcome Measuresmentioning
confidence: 99%